Medicines shortages in Pakistan: a qualitative study to explore current situation, reasons and possible solutions to overcome the barriers - Iram Malik; Irem Mushtaq; Saima Asghar (BMJ Open)
Objective This study was conducted to assess current situation of medicines shortages in Pakistan and to identify its impact, reasons and possible solutions to overcome the barriers.Design A qualitative study.Setting The study was conducted between May 2018 and July 2018 in three cities of Pakistan including Islamabad, Karachi and Bahawalpur, depending on the availability of most relevant key informants.Participants Health regulators, pharmaceutical manufacturers, pharmaceutical distributors and pharmacists.Primary and secondary outcome measure Study primarily explored current situation, reasons and potential solutions of medicines shortages in Pakistan. Secondary outcome was the issue of particular brand shortage.Method Semistructured interviews were conducted. Sample size was determined by using saturation point criteria. Convenient sampling techniques were used to recruit the participants. The interviews were audiorecorded and transcribed verbatim. Data were analysed using inductive thematic analysis.Results A total of 41 stakeholders including 12 health regulators, 6 pharmaceutical manufacturers, 8 pharmaceutical distributors and 15 pharmacists participated in this study. Data analysis yielded 4 themes, 16 subthemes, 51 categories. Essential and life-saving medicines were in short supply. The major reasons of short supply of medicines were active pharmaceutical ingredient and raw material availability issues, lack of traditional distribution system and sudden demand fluctuation. Among proposed solutions, three most common were the facilitation and regulation of manufacturers, reasonable price fixation and improvements in the inventory control system.Conclusion Medicines were short in supply, and this may have clinical and financial impact on the patients in Pakistan. There were multiple and complex reasons of medicines shortages. Mandatory government leadership is required to resolve the issue on priority basis for improving the access of medicines to the patients.